The Impact of Islamic Conflict in Pattani Thailand - Nulhasanah, Lisan (Jurnal Kawasan Sejarah, 2023)
Social, economic and educational aspects are all affected by the Pattani Islamic conflict in Thailand. In terms of social impact, the conflict damaged social structures, fractured communities and caused psychological trauma. The threat of terror and insecurity disrupted social balance, undermined the sustainability of local culture, and halted individual development. Economically, the conflict damaged the economic structure of the south, especially in the agriculture and trade sectors. As a result, incomes fell, unemployment rose, and poverty increased. The research method used in this study was conducted by combining several research methods. Literature review, survey and case study were used to understand the issue in West Asia. The results showed that the Pattani Islamic Conflict affected many areas in southern Thailand. To ease the impact, everyone must commit to peace, economic and social recovery, and access to good education. To achieve a stable, prosperous, and sustainable future, governments, communities, and the international community must work together.